(untitled) (Research, Society and Development, 2020)
This article aims to verify the relationship between the characters of the IT franchise and the psychoanalytic theories of the psychic structuring. Based on a qualitative exploratory research, a film analysis of the traumas and fears of the characters was carried out in the movies “It” (2017) and “It - Chapter Two” (2019) associated with the concepts of repression, symptoms such as hallucinations, and return of repression. Based on the psychoanalytical theoretical reference, it was possible to analyze three characters: Beverly, who deals with puberty issues and an abusive father, hearing voices in the bathroom and watching blood coming out of the sink as a teenager, and as an adult married a man who possesses traits of his father. Ben, a new boy in town, struggling to fit in, and during a visit to the library comes across a dismembered person, and when older drowns on land asking for help without anyone listening to him. And Bill who feels guilty about the disappearance of his younger brother, reliving his trauma years later, but this time as if he was actually guilty, watching his brother like a puppet he holds himself. Such situations appear as return of repression, and hallucinations symptonms, reemerging as adults. In this way, the research was able to explore the theoretical concepts relating them to the chosen characters and scenes, and made it possible to observe that even having a complexity, it is possible to relate everything we consume with psychoanalytic theory, whether books, serials and movies.